Some features of concentration oscillations in the phenylacetylene oxidative carbonylation reaction - S. N. Gorodsky; K. Novakovic (Тонкие химические технологии, 2010)
Some modes of concentration oscillations in the homogeneous system KI-PdI2-CO-O2-CH3OH are described in this paper. Described modes of phenylacetylene oxidative carbonylation reaction in this system have some distinctive features. The further studies would reveal the reasons of these special modes and help one to understand in more details the mechanism of concentration oscillations of unsaturated compounds occurring in the carbonylation reactions.